Antagonism of Paecilomyces spp. isolated from banana (Musa spp.) roots and rhizosphere against Radopholus similis - Kilama, P.; Dubois, T.; Coyne, Danny L.; Niere, B.; Gold, Cliford S.; Adipala, E. (2007)
Banana (Musaspp.) in East Africa is threatened by pests and diseases, of which the burrowingnematode, Radopholus similis, is among the most serious and difficult to control. Fungal antagonists, such as Paecilomyces spp., can aid in controlling R. similis. In this study, Paecilomyces spp. was isolatedfrom banana roots and rhizosphere in fields in Uganda with high and low densities of R. similis. Fungi were more abundant in the rhizosphere than on roots in the field with low R. similis density, whereas the reverse occurred in the field with high R. similisdensity. A total of 23 isolates of Paecilomyces spp. were collected, of which Paecilomyces lilacinuswas the most abundant species. This is the first reportshowing the high presence of Paecilomycesspp. in the rhizosphere of bananas. Bioassays revealed thatfiltrates of P. lilacinusand Paecilomyces marquandii caused reversible paralysis of male and juvenileR. similis. Paecilomyces lilacinus isolate 23N5-2 caused greatest paralysis, which was not influenced by filtrate concentration.